On consistent statistical procedures in regression - Yatracos, Yannis G. (My University, 2006)
Necessary and sufficient conditions are provided for the existence of consistent statistical procedures in regression models with random predictors under various error assumptions.
Keywords: Statistics; Error analysis (Mathematics); Mathematical models